Taxonomic revision of Australasian diving beetles in the genus Leiodytes Guignot, 1936 (Coleoptera: Dytiscidae, Bidessini) - Hendrich, Lars; Wang, Liang-Jong; Balke, Michael (Zootaxa, 2021)
Bidessus migrator Sharp, 1882, so far assigned to Clypeodytes Régimbart, 1894, and widely distributed in Australia and New Guinea, is re-described. Based on morphological and molecular evidence, it is here transferred to Leiodytes Guignot, 1936. Bidessus loriae Régimbart, 1892 is found to be a junior subjective synonym of L. migrator. We describe the following new species: Leiodytes surianiae sp. nov. (eastern New Guinea, northeast coast of Queensland), and Leiodytes wattsi sp. nov. (southern New Guinea and Darwin area to northern Queensland). We delineate the species using characters such as male genital structure and beetle size, shape and color pattern. Mitochondrial Cox1 data for 27 individuals, representing all three Australasian species, were generated and revealed clusters congruent with the morphological evidence. In Australia Leiodytes only occurs in the tropical and subtropical northern part of the continent. None of the species is endemic to Australia. The species are mainly lentic, occurring in seasonal swamps, flooded meadows and pools of intermittent rivers and temporary creeks.